312 Combination therapy of oral cyclophosphamide and bevacizumab for patients with recurrent ovarian and peritoneal cancer. (13th November 2020) - Goto, M; Takimoto, Y; Isono, R; Yamashita, M; Onoue, M; Yoshioka, E; Tashima, R; Hori, K; Tsubamoto, H; Ito, K
Abstract : Objective: The purpose of chemotherapy for recurrent cancer is to get survival benefit, relieve symptoms, and improve quality of life. We used oral cyclophosphamide (CPA) and bevacizumab (BEV) combination therapy in cases of recurrent ovarian and peritoneal cancer, where standard chemotherapy was difficult to conduct. We subsequently evaluated the safety and efficacy of this treatment. Methods: Between August 2014 and June 2020, subjects who provided informed consent received the following regimen: oral CPA 50 mg daily and intravenous BEV15 mg/kg every 3 weeks as 1 cycle. Data from the two facilities were retrospectively studied. Result: Twenty-two patients were enrolled (20 with ovarian cancer and 2 with peritoneal cancer). The median follow-up period was 18.9 months (range, 5.0–51.5), and median age was 60 years (range 37–81). Sixteen patients had platinum resistance. The median number of previous chemotherapy regimens was 2.5 (range 0–5). The median implementation cycle was 5 (range 2–14). Eighteen patients discontinued treatment: three due to side effects, and fifteen due to disease progression. Grade 2 toxicities included neutropenia (1), protein urea (1), hypertension (2), and esophagitis (1). Two patients had a complete response, and one patient had a partial response. Five patients had stable disease. The response rate was 13.6%. Median PFS was 5.3 months (range, 0.8–23.5). The median OS from the initiation of CPA/BEV was 9.2 months (range, 4.8–51.5+). Conclusions: The combination therapy of oral cyclophosphamide and bevacizumab had relatively effective, and can be used safely in patients who have become difficult to treat after second-line chemotherapy.